Politics does not exist: metaphors, politics and political study (Economic and Political Thought, 2016)
Metaphors do not only describe reality; in some cases they even create it.Western social theories – inspiring political scientists – promoted a peculiarDecalogue of specific metaphors: the society as a biological system, a machine,a market, a battlefield, a legal order, a game, a theatre, a discourse, an establishedhierarchy and a race for life. Contrasting policy with ethics occurs withparticular strength when one begins to treat the very concept of politics asa metaphor. The theory of international relations in its foundations is based ona relatively small number of categories that are by their very nature metaphors.Politics as a purposeful activity, the search for a compromise, the mechanismthat maintains society as a whole, does not exist in the modern world.